(untitled) (Research, Society and Development, 2020)
This ecological, analytical and exploratory study aimed to characterize patients diagnosed with neglected diseases in Picos, Piauí and exemplify how the association of a tool of a geographic information system with specific knowledge can bring contributions to public health decisions. The study was carried out using data from the Epidemiological Surveillance. The presence of global spatial dependence was verified through the global Moran index and was evaluated by local autocorrelation through LISA (Local Indicators of the Space Association). For spatial representation of the Moran scattering diagram, Moran Maps were used. The evidenced information made possible the comprehension of the local epidemiology and, the geoprocessing techniques allowed the visualization of the cases of neglected diseases distributed in the city. In the urban network, there was a cluster of neighborhoods with similar incidence rates in neighborhoods close to the downtown. A high-risk cluster was identified in the central neighborhoods of the city, enabling the identification of vulnerable areas and providing visibility in disease detection rates by neighborhood, thus providing information that would not be visualized working only with tabular data.